Association Analysis of WNT3, HLA-DRB5 and IL1R2 Polymorphisms in Chinese Patients With Parkinson’s Disease and Multiple System Atrophy - Su, Wei-Ming; Gu, Xiao-Jing; Hou, Yan-Bing; Zhang, Ling-Yu; Cao, Bei; Ou, Ru-Wei; Wu, Ying; Chen, Xue-Ping; Song, Wei; Zhao, Bi; Shang, Hui-Fang; Chen, Yong-Ping (Frontiers in Genetics, 2021)
Background: The association between inflammation and neurodegeneration has long been observed in parkinson’s disease (PD) and multiple system atrophy (MSA). Previous genome-wide association studies (GWAS) and meta-analyses have identified several risk loci in inflammation-associated genes associated with PD. Objective: To investigate whether polymorphisms in some inflammation-associated genes could modulate the risk of developing PD and MSA in a Southwest Chinese population. Methods: A total of 2,706 Chinese subjects comprising 1340 PD, 483 MSA and 883 healthy controls were recruited in the study. Three polymorphisms (rs2074404 GG/GT/TT, rs17425622 CC/CT/TT, rs34043159 CC/CT/TT) in genes linked to inflammation in all the subjects were genotyped by using the Sequenom iPLEX Assay. Results: The allele G of WNT3 rs2074404 can increase risk on PD (OR: 1.048, 95% CI: 1.182–1.333, p = 0.006), exclusively in the LOPD subgroup (OR: 1.166, 95% CI:1.025–1.327, p = 0.019), but not in EOPD or MSA. And the recessive model analysis also demonstrated an increased PD risk in GG genotype of this locus (OR = 1.331, p = 0.007). However, no significant differences were observed in the genotype distributions and alleles of HLA-DRB5 rs17425622 and IL1R2 rs34043159 between the PD patients and controls, between the MSA patients and controls, or between subgroups of PD or MSA and controls. Conclusion: Our results suggested the allele G of WNT3 rs2074404 have an adverse effect on PD and particularly, on the LOPD subgroup among a Chinese population.